(untitled) (Bangladesh Journal of Agricultural Research, 2015)
A field experiment was carried out during Rabi seasons of 2011-12 and 2012-13 to evaluate the efficacy of fungicides in controlling Stemphylium blight (S. botryosum) of lentil. Five fungicides were evaluated under higher disease pressure (106 ml-1) of Stemphylium blight. Results revealed that Foliar spray (4 sequences) with Rovral 50WP (Iprodione) @ (0.2%) and Secure 600WG (Fenamidione+Mancozeb) @ (0.2%) at an interval of 7 days effectively controlled the disease and increased yield of lentil by 31.99% and 28.20%, respectively. The fungicides may be selected for control of the disease. Bangladesh J. Agril. Res. 40(2): 229-233 June 2015